Understanding the Perspectives and Usability of Digital games for Children with Intellectual Disabilities - Dhiyaneshwari RP; Renuga Devi C (Journal of Applied Engineering and Technological Science (JAETS), 2023)
Typically, the digital games are used as a medium for teaching students having intellectual disabilities, and it helps the student to enhance their learning skills and to understand their surroundings. Intellectual disability is a neurological disease that manifests as a deficit in an individual's mental and adaptive functioning during childhood. Moreover, the computer-assisted training has been shown to be the most effective method of instruction for children with disabilities in terms of conceptual learning, academic accomplishment, and skill-based development. Traditionally, some existing research works are done in this field for analyzing the effectiveness of digital games. Accordingly, the main contribution of this research work is to determine the perception of special educators and usability of digital games in educational settings for children with intellectual disabilities. By identifying the needs for their design and use in those children's classes, this study intends to further illuminate how to employ digital games in education as a contribution to improving educable intellectually impaired children's teaching and learning practices. In addition, a case study is conducted in this work using a closed-ended questionnaire on a sample of 60 special educators, handling Children with Intellectual disabilities. According to this case study analysis, the quantitative analysis suggest that special educators have a strong need to use digital games to optimize learning for children with intellectual disabilities and to promote digital inclusion. Based on the outcomes, it is inferred that the digital game based learning could be more helpful and beneficial for the student with intellectual disabilities in real time.